The ASQ certified medical device auditor handbook - Laman, Scott A., 1962- (ASQ Excellence, 2021)
"Regulations and guidance affecting the medical device industry continually evolve. Although new or updated requirements may be introduced at any time, revisions to the exam Body of Knowledge (BoK), reference list, and exam maintain their five-year review cycle. Consequently, contents of this Handbook and CMDA certification differ from the current state of the medical device industry. The fourth edition of The Medical Device Auditor Handbook, as a primary source of information for certification exam preparation, correlates to the 2020 certification exam BoK and reference list. This edition has been reorganized to align more closely with the BoK and includes a significant amount of brand-new material. The combination of this publication and reference materials is intended to provide a well-rounded background in medical device auditing"--